PEMANFAATAN PLATFORM DIGITAL OLEH DISKOMINFO BANYUMAS: STRATEGI PEMERINTAH KABUPATEN DALAM MENGHADAPI ERA NEW MEDIA - Ana Fitrotul Lisa Ana Fitrotul Lisa; Anas Azhimi Qalban (Jurnal Komunikasi dan Media, 2025)
This research discusses the communication strategy of the Banyumas Regency Government through the Communication and Information Agency (Diskominfo) in utilising digital platforms to address the challenges of the new media era. The research uses a descriptive qualitative approach with literature study and documentation methods. The results indicate that Diskominfo Banyumas implements a strategy based on the Lasswell model, which includes the communicator, message content, media, audience, and effects. Platforms such as Instagram, the official website, and collaborations with local media are utilised to enhance digital literacy and reach a wide audience. The conclusion suggests that this strategy is effective in increasing public participation and strengthening digital government communication.